3D Morphology Distribution Characteristics and Discrete Element Simulation of Sand-Gravel Mixtures. (22nd November 2021) - Qi, Wu; Suyu, Sun; Guangliang, Gao; Yi, Fang; Guoxing, Chen
Abstract : Sand-gravel mixtures are typical binary materials, exhibiting highly heterogeneous, discontinuous, and significant structural effects. The contact state between sand and gravel particles has a significant influence on the mechanical properties of the mixtures. This article focused on the complex internal structure and its mesostructural behavior of the mixtures, and a systematic statistical analysis was carried out to study the shape, size, and angularity of the coarse particles. The three-dimensional (3D) shapes of coarse aggregates were approximated to be hexahedron, pentahedron, and tetrahedron. An indicator called angularity and surface texture (AT) index was developed to characterize the combined effect of the coarse aggregate angularity and surface texture. Based on the screening testing and digital image processing, the particle size and AT index of aggregates were extracted, and their means, standard deviations, and statistical distributions were studied. An algorithm for generating 3D aggregates was developed based on the statistical results of the coarse aggregate 3D morphology. The coarse aggregate generating code was written using the fish language in PFC3D. The numerical model was then applied to conduct three typical monotonic or cyclic triaxial test simulations. Retrospective simulation of the laboratory tests using the proposed model showed good agreement, and the reliability of the model is effectively verified. The results interpreted well the mechanism of particle motion and the distribution of interparticle contact force during shearing from mesoscale of the mixtures, which can give better understanding and modeling of the nonlinear behavior of the sand-gravel mixtures.